Obesity among females in Al-Sader city Baghdad, Iraq, 2017. - Jasim, Hadeel M.; Abdul Hussein, Hassan M.; Al-Kaseer, Eman A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: obesity is a serious public health problem. Literatures in Iraq explained that obesity due to change in economy and Lifestyles. Objective: To report on prevalence of obesity among women in Al- sader City, Baghdad. 2017. Method: A total of 440 females were included in this study. They were Selected randomly from relatives to patients accompanied them In attending to primary health care centers. BMI (body mass index) to assess the Weight. Demo-graphic data were requested too. Result: The prevalence of obesity was 35.2%. Age , education, divorced Widows were determinants of obesity. Employment and crowding Index (socioeconomic status) were not obvious determinants of obesity. Conclusion: High prevalence of obesity was observed.